Fibrinolytic potential as a risk factor for postpartum hemorrhage - Gruneberg, Daniel; Braun, Paula; Schöchl, Herbert; Nachtigall-Schmitt, Tereza; Forst, Maik von der; Tourelle, Kevin M.; Dietrich, Maximilian; Wallwiener, Markus; Wallwiener, Stephanie; Weigand, Markus A.; Fluhr, Herbert; Spratte, Julia; et al. (Frontiers in medicine, 2023)
BackgroundPostpartum hemorrhage (PPH) is still the leading cause of maternal morbidity and mortality worldwide. While impaired fibrin polymerization plays a crucial role in the development and progress of PPH, recent approaches using viscoelastic measurements have failed to sensitively detect early changes in fibrinolysis in PPH. This study aimed to evaluate whether women experiencing PPH show alterations in POC-VET fibrinolytic potential during childbirth and whether fibrinolytic potential offers benefits in the prediction and treatment of PPH.MethodsBlood samples were collected at three different timepoints: T0 = hospital admission (19 h ± 18 h prepartum), T1 = 30-60 min after placental separation, and T2 = first day postpartum (19 h ± 6 h postpartum). In addition to standard laboratory tests, whole-blood impedance aggregometry (Multiplate) and viscoelastic testing (VET) were performed using the ClotPro system, which included the TPA-test lysis time, to assess the POC-VET fibrinolytic potential, and selected coagulation factors were measured. The results were correlated with blood loss and clinical outcome markers. Severe PPH was defined as a hemoglobin drop > 4g/dl and/or the occurrence of shock or the need for red blood cell transfusion.ResultsBlood samples of 217 parturient women were analyzed between June 2020 and December 2020 at Heidelberg University Women's Hospital, and 206 measurements were eligible for the final analysis. Women experiencing severe PPH showed increased fibrinolytic potential already at the time of hospital admission. When compared to non-PPH, the difference persisted 30-60 min after placental separation. A higher fibrinolytic potential was accompanied by a greater drop in fibrinogen and higher d-dimer values after placental separation. While 70% of women experiencing severe PPH showed fibrinolytic potential, 54% of those without PPH showed increased fibrinolytic potential as well.ConclusionWe were able to show that antepartal and peripartal fibrinolytic potential was elevated in women experiencing severe PPH. However, several women showed high fibrinolytic potential but lacked clinical signs of PPH. The findings indicate that high fibrinolytic potential is a risk factor for the development of coagulopathy, but further conditions are required to cause PPH.
Gesehen am 25.09.2023